C. McGinn. Is Romantic Self-Love Possible? / trans. from Engl. A. V. Nekhaev - A. V. Nekhaev (Омский научный вестник: Серия "Общество. История. Современность")
The essay examines the metaphysical possibility of romantic self-love. It makes difference between two forms of such love feeling like de re and de dicto. Based on this difference, the impossibility of romantic self-love de dicto is demonstrated, since this would violate one of the constitutive conditions of such a love feeling — the requirement of the numerical distinctness between the lover and the beloved.